Student-Athletes: How Do They Cope? - Miller, Gary; Pappas, Jason C. (My University, 2003)
The ways student-athletes cope with academic and athletic situations on campus was discussed in this paper. The authors examined four models (moral, compensatory, medical, and enlightenment) for helping and coping that have direct application to working with student-athletes. They also presented the SPORT goal-setting model and discuss implications for athletic academic advisors. S: State what you want to have happen; P: Performance expected of you to accomplish this; O: Organize yourself for success by doing; R: Reality Check - Yes I can/No I can not; T: Time table for completing your goal
Keywords: skills; academic support; models